MICROBIAL CONSORTIA OF FUNGAL AND BACTERIAL COCULTURES INCREASES BIODEGRADATION RATE OF POLYCYCLIC AROMATIC HYDROCARBONS - SWAPNA GUNTUPALLI; V B S C THUNUGUNTLA; RAO CV; BONDILI JS (International Journal of Pharma and Bio Sciences, 2016)
Isolation and characterization of polycyclic aromatic hydrocarbons (PAHs) degrading microorganisms from contaminated sites is well studied. A single organism having the potential to degrade different PAHs is exceptional and hence in the present study, the PAHs degradation capacity of a microbial consortium consisting of fungal, bacterial cocultures was evaluated. Within 7 days, consortium showed 99%, 57.4%, 60% and 82% degradation of Phenanthrene (PHE), Pyrene (PYR), Fluoranthene (FLU) and Chrysene (CHY), each PAH of 100mg/L concentration respectively. The culture broth was analyzed for the presence of degradation metabolites by GC-MS and the enzymes produced by the consortium. Coexistence of three metabolic pathways, cytochrome P450 monooxygenase with the detection of epoxy derivatives, catechol by bacterial dioxygenases and via Quinones of ligninolytic pathway were identified. Concurrently, microbial consortia also demonstrated good biosurfactant production capacity in the presence of PAHs. These results highlight that the microbial consortium can be of potential use with increased rate of bioremediation of PAHs cometabolically.